Effect of video-assisted structured teaching program on knowledge of breast self-examination among female college students of Puducherry: a pre and post experimental study - Mathew, Neethu Mariya; Ramakrishnan, Jayalakshmy; Venkatesan, Yamuna Thirvanthipuram; Chandar, Deepika (International Journal Of Community Medicine And Public Health, 2020)
Background: Breast self-examination (BSE) is an easy method for early detection of breast cancer that can be performed by self at home. The present study was done to assess the effect of video-assisted structured teaching program on knowledge of BSE among female college students of Puducherry. Methods: This pre and post experimental study was conducted in September 2014 among 160 college students at government women’s college, Puducherry who were aged 18-26 years. The knowledge was assessed using a pre-tested semi-structured questionnaire following which breast self-examination techniques were taught to them using a video. The post-assessment was done after 14 days of teaching program using the same tool. Results: Of the 160 participants, 90% were undergraduates, 85.6% were Hindus, 58.1% were from rural area and 5.6% were having family history of breast cancer. The knowledge regarding the breast cancer was good even before the intervention and the media was the main source of information. The video-assisted structured teaching used in this study was effective to improve the overall awareness score for breast cancer and BSE significantly. The change in knowledge regarding the steps and the pattern of performing BSE was not statistically significant. Conclusions: The video-assisted teaching used was found to be effective in improving the knowledge regarding BSE. This type of regular health education with short videos can be a useful method for imparting knowledge to college students about BSE. However, the exact technique of performing BSE needs further reinforcement among the study participants.